Bleak house, with ebook eaudiobook - Dickens, Charles (Tantor Media, 2009)
Widely regarded as Dickens's masterpiece, Bleak House centers on the generations-long lawsuit Jarndyce and Jarndyce , through which "whole families have inherited legendary hatreds." Focusing on Esther Summerson, a ward of John Jarndyce, the novel traces Esther's romantic coming-of-age and, in classic Dickensian style, the gradual revelation of long-buried secrets, all set against the foggy backdrop of the Court of Chancery. Mixing romance, mystery, comedy, and satire, Bleak House limits the suffering caused by the intricate inefficiency of the law.